Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I am suppose to differentiate

$y=(\sin x)^{\ln x}$

I have absolutely no idea, this was asked on a test and I just do not know how to do this I have forgotten the tricks I was suppose to memorize for the test.

share|cite|improve this question
If you take the logarithms of both sides, you have $\ln\,y=(\ln\,x)(\ln\sin\,x)$. You can use implicit differentiation, the chain rule, and the product rule from here. – J. M. May 4 '12 at 14:48
I don't have those things memorized anymore. Also I don't know where the lnx went. – user138246 May 4 '12 at 14:51
You may not have them memorized, but you can look them up: implicit differentiation, the chain rule and the product rule. – Chris Taylor May 4 '12 at 14:59
Unsolicited advice: "memorizing" everything, and "reviewing without looking things up" are generally bad study policies. – rschwieb May 4 '12 at 15:03
@Jordan $y=(\sin x)^{\ln x}$ means that $y$ is $\sin x$ raised to the $\ln x$ power, while $\sin x^{\ln x}=\sin (x^{\ln x})$. – Américo Tavares May 4 '12 at 16:52
up vote 5 down vote accepted


$$\sin x=e^{\ln \left( \sin x\right) }\Rightarrow \left( \sin x\right) ^{\ln x}=\left( e^{\ln \left( \sin x\right) }\right) ^{\ln x}=e^{\left( \ln x\right) \;\cdot\;\ln \left( \sin x\right) }\tag{1}$$

and evaluate the derivative of $e^{\left( \ln x\right) \ln \left( \sin x\right) }.$

Comments (trying to reply to OP's comments).

  1. We can start by writing the given function as $$y=(\sin x)^{\ln x}=e^{\left( \ln x\right) \;\cdot\;\ln \left( \sin x\right)},\tag{2}$$ which is a particular case of the algebraic identity $$\left[ u\left( x\right) \right] ^{v\left( x\right) }=e^{v(x)\;\cdot\;\ln(u(x))}.\tag{3}$$ Remarks. We've used the following properties. By the definition of the natural logarithm, we have (see Powers via logarithms) $$\ln u=v\Leftrightarrow u=e^v=e^{\ln u},\tag{4}$$ and the rule $(a^b)^c=a^{b\;\cdot\; c}\tag{5}$
  2. Finally we evaluate the derivative of $e^{g(x)}$, where $$g(x)=\left( \ln x\right)\;\cdot\; \ln \left( \sin x\right)\tag{6}.$$ By the chain rule we have $$y'=(e^{g(x)})'=e^{g(x)}g^{\prime }(x),\tag{7}$$ and $g'(x)$ is to be computed by the product rule.

Evaluation of $(7)$ $$\begin{eqnarray*} g^{\prime }(x) &=&\left( \left( \ln x\right) \ln \left( \sin x\right) \right) ^{\prime } \\ &=&\left( \ln x\right) ^{\prime }\ln \left( \sin x\right) +\left( \ln x\right) \left( \ln \left( \sin x\right) \right) ^{\prime } \\ &=&\frac{1}{x}\ln \left( \sin x\right) +\left( \ln x\right) \frac{\cos x}{ \sin x} \\ &=&\frac{\ln \left( \sin x\right) \sin x+\left( \left( \ln x\right) \cos x\right) x}{x\sin x}.\tag{8} \end{eqnarray*}$$

Hence, since $e^{g(x)}=\left( \sin x\right) ^{\ln x}$, we obtain $$\begin{eqnarray*} y^{\prime } &=&e^{g(x)}g^{\prime }(x)=y\;\cdot\; g^{\prime }(x) \\ &=&\left( \sin x\right) ^{\ln x}\frac{\ln \left( \sin x\right) \sin x+\left( \left( \ln x\right) \cos x\right) x}{x\sin x}.\tag{9} \end{eqnarray*}$$

share|cite|improve this answer
$e^x$ and $\ln x$ are inverse functions. Therefore, $e^{\ln u}=u$. Then for the second part, $(a^b)^c=a^{bc}$. The function should now be in a form where you can take the derivative. – Mike May 4 '12 at 15:40
@Jordan No, $e^{\ln x}=x$ – Américo Tavares May 4 '12 at 16:41
@Jordan I've thought evaluating the derivative of $e^{\text{some function of } x}$. So I converted the given function $y=(\sin x)^{\ln x}$ to that form. I started by writing $\sin x$ as $e^{\ln(\sin x)}$. – Américo Tavares May 4 '12 at 16:55
@Jordan $\ln x$ is the exponent of $\sin x$. So, after converting $\sin x$ to $e^{\ln (\sin x)}$, we have to multiply the exponents $\ln x$ and $\ln (\sin x)$. – Américo Tavares May 4 '12 at 17:13
@Jordan Because of the power rule $(u^v)^w=u^{v\cdot w}$ mentioned in 2, applied to $u=e, v=\ln(\sin x), w=\ln x.$ – Américo Tavares May 4 '12 at 17:39

You can either use the definition that says that $$a^b = e^{b\ln(a)}$$ and use the chain rule with $$y(x) = (\sin x)^{\ln x} = e^{(\ln(x))(\ln(\sin x))}$$ or you can use logarithmic differentiation.

If $y = (\sin x)^{\ln x}$, then taking logarithms on both sides we get $$\ln y = \ln\left((\sin x)^{\ln x}\right) = (\ln x)\ln(\sin x).$$ Now using implicit differentiation we have: $$\begin{align*} \frac{d}{dx}\ln y &= \frac{d}{dx}\left( (\ln x)\ln(\sin x)\right)\\ \frac{1}{y}\frac{dy}{dx} &= \left(\ln x\right)'\ln(\sin x) + (\ln x)\left(\ln (\sin x)\right)'\\ \frac{y'}{y} &= \frac{1}{x}\ln(\sin x) + (\ln x)\left(\frac{1}{\sin x}(\sin x)'\right)\\ \frac{y'}{y} &= \frac{\ln\sin x}{x} + \frac{(\ln x)\cos x}{\sin x}\\ \frac{y'}{y} &= \frac{\ln \sin x}{x} + \ln x\cot x\\ y' &= y\left(\frac{\ln \sin x}{x} + \ln x\cot x\right)\\ y' &= (\sin x)^{\ln x}\left(\frac{\ln \sin x}{x} + \ln x\cot x\right). \end{align*}$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.